Selective Oxidation of Sulfides in Flow Chemistry. Issue 18 (11th May 2018) - Silva, Filipa; Baker, Alastair; Stansall, James; Michalska, Weronika; Yusubov, Mehkman S.; Graz, Michael; Saunders, Robert; Evans, Gareth J. S.; Wirth, Thomas
Abstract : A packed‐bed reactor with oxone has been employed for selective oxidations of sulfur compounds. Various sulfides containing different functional groups are efficiently oxidized to the corresponding sulfoxides without formation of sulfones or other side products. Abstract : A selective sulfide oxidation has been achieved in flow chemistry by using fixed‐bed oxone reactors.